Edukasi Vaksinasi Covid 19 untuk Pelajar MA MA’ARIF Guna Mencapai Kekebalan Komunal - Novriyanti Lubis; Novita Rosalia; Sution; Putri Widia; Robi Asran Nugraha; Syifa Aladawi; Ikbal Taufikurohman (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Vaccination is a medical prevention that is considered as one of the latest breakthroughs in the world of health because it is preventive so that it can save human lives, especially during the current Covid 19 pandemic. Starting from the new academic year 2021, the government is trying to organize face-to-face learning, one of the conditions for these activities to be carried out properly, it is recommended that students should be vaccinated first. Madrasah Aliyah Ma'arif is one of the schools that has held offline learning, but no students have been vaccinated as of September 2021, Group 4 KKN Cikelet village wants to contribute to the success of vaccination for students, one of which is by providing health education where the topic given is the importance of being vaccinated. The activity begins with pre-test, counseling and post-test. The expected output is an increase in students' knowledge about vaccines and the number of students who are willing to be vaccinated so that face-to-face learning can take place safety and well.